Formação continuada colaborativa na escola: uma intervenção na ação alfabetizadora com ênfase à utilização dos textos como unidade básica de ensino no processo de alfabetização de crianças - SILVA, Francisca Das Chagas Dos Passos (2018)
This research, titled: “CONTINUOUS COLLABORATIVE TRAINING IN SCHOOL: an intervention in literacy action with emphasis on the use of texts as a basic unit of teaching in the process of children's literacy," has as a general objective to understand every process of organization, planning, implementation and evaluation of a continuing education course based on the contributions of collaborative action research with the teachers of the Blue School literacy cycle focusing on the teaching of written language using text as a basic unit for teaching. In order to orient / systematize our research trail, the specific orienting objectives pointed to those that follow: Systematize the theoretical contributions on the paradigms of continuous formation that guide the formative actions in the schools, as well as those that mark the work with texts as a discursive genre in the teaching of written language in the literacy cycle; To verify how the pedagogical work has been developed with the text for the teaching of written language in the classes of the literacy cycle of the school of the municipal network of São Luís / MA; To develop a continuing training course for female teachers focusing on the use of text as a basic unit for the teaching of written language in literacy, and to produce a Training Portfolio from the intervention - with the course of continuing education developed with the with the purpose of sharing the results of a collaborative formative experience. The theoretical and methodological reference framework of the Research that gave an account of the scope of the proposed objectives, runs through the applied research (BERVIAN, CERVO, 1996) of the intervention type (DANIANI, 2012), based on collaborative action research. The theoretical contributions that underpinned the analyzes for the basis of the questions concerning written language were: Vigotsky (1989 and 1995) ), Gerald (2002, 2011), Bakhtin (1995), Suely Mello (2010), Magda Soares (1986), Lerner (2002), Kaufman (1995), Kleiman (2000), Smolka (2012), Goulart e Souza (1995), Marcuschi (2011), and the course of research on teacher education, such as Candau (1997), Nóvoa (1991, 2005), Tardif (2012), Pimenta (1997), Gauthier , Zainko (2006), Imbernón (2011), and others were decisive for our purposes. The results showed that the process of sustained intervention in collaborative research was very significant, since it enabled the collaborating teachers and the researchers to coordinate interactions, experiences and the certainty that the collaborative formative model we are experiencing is a path to be pursued in educational research, look at the school, the classroom and their teachers. To analyze and allow them to reflect on their knowledge, in the use of the text as a basic unit of Portuguese Language teaching showed that teachers understand the training process with emphasis on their important practices, with necessary sense and feel more sensitized and available to to re-signify their knowledge with results in the practice of the classroom. We affirm that at the conclusion of the planned reflective sessions, they have left us with a perception that the reflexive formative process is indispensable.